Radiotherapy of prostate and head-and-neck tumour: an optimal treatment planning comparison for intensity modulated radiotherapy and volumetric modulated arctherapy techniques - Ghulam Murtaza (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate and compare merits between intensity modulated radiotherapy and volumetric modulated arc-therapy radiotherapy techniques to determine which technique can achieve better treatment plan quality and efficient delivery. Method: The retrospective study was conducted at the Radiation Oncology Department of SanBorotlo Hospital, Vicenza, Italy, in 2019, and comprised data from Jan 2019 to Dec 2019 related to prostate and head-and-neck patients in whom Pinnacle³ treatment planning system was used for optimisation with different prescribed doses and target geometries for intensity modulated radiotherapy and volumetric modulated arc-therapy techniques. Treatment plans were simulated using 6MV photon beam of SynergyS® Linac (Linear accelerator). The plan quality was evaluated using dose-volume indices for planning target-volume and organs-at-risk. ArcCHECK™ phantom was used for dose agreement verification between planed and delivered doses. Results: Data of 8 patients was analysed. Intensity modulated radiotherapy and volumetric modulated arc-therapy treatment plan quality for prostate was found to be similar, but volumetric modulated arc-therapy had significant results for maximum dose (p=0.005). Intensity modulated radiotherapy and volumetric modulated arc-therapy plans for head-and-neck achieved adequate target coverage and sparing of organs at risk, and produced clinically acceptable treatment plans. The percentage of target coverage (p=0.001), dose maximum (p=0.013) and conformity index (p=0.000) were significant. A significant gain for all planning target volume dose-volume indices was noted (p<0.05). Volumetric modulated arc-therapy obtained better plan with significant values and improved sparing of organs at risk compared to intensity modulated radiotherapy for both prostate and head-and-neck treatments while maintaining doses to the organs at risk (p<0.05). Conclusion: Dynamic arc mode of beam delivery provided increased degrees of freedom of volumetric modulated arc-therapy beam intensity modulation, depicting superior dose distribution than intensity modulated radiotherapy. Key Words: IMRT, VMAT, Radiotherapy, Treatment planning.